2017
DOI: 10.1111/jog.13238
|View full text |Cite
|
Sign up to set email alerts
|

Urologic injuries during gynecologic surgery, a 10‐year review

Abstract: Urinary bladder injury was the most common urinary tract injury during gynecologic surgery. Previous pelvic surgery and the presence of adhesion were significant risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 17 publications
1
19
0
1
Order By: Relevance
“…The literature data regarding this issue is conflicting. In some studies, the highest incidence has been found with abdominal hysterectomies (17,18), but others reported a higher incidence with laparoscopic hysterectomies (19,20). In contrast, in a prospective study by Ibeanu et al (7), the authors reported that the vaginal hysterectomy was associated with more ureteric injuries (2.6%) than abdominal (1.7%) and laparoscopically assisted vaginal hysterectomies (0%), in accordance with our experience.…”
Section: Discussionsupporting
confidence: 87%
“…The literature data regarding this issue is conflicting. In some studies, the highest incidence has been found with abdominal hysterectomies (17,18), but others reported a higher incidence with laparoscopic hysterectomies (19,20). In contrast, in a prospective study by Ibeanu et al (7), the authors reported that the vaginal hysterectomy was associated with more ureteric injuries (2.6%) than abdominal (1.7%) and laparoscopically assisted vaginal hysterectomies (0%), in accordance with our experience.…”
Section: Discussionsupporting
confidence: 87%
“…The risk of bladder injury can be minimized at the outset of the procedure by retrograde filling, which allows the superior edge of the bladder to be identified (Wang et al, ). Injuries to the urinary bladder are the most common urinary tract complications in gynecological surgery and the risk could be lowered through a careful preoperative medical history, since the injury risk is associated with previous pelvic surgery and related adhesions (Satitniramai and Manonai, ). Care should be taken with the paravesical tissue during the anterior approach as it contains the vesical venous plexus, which consists of 2–5 main vein rows directly lateral to the bladder with various anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…Using the posterior approach, it is crucial to visualize the ureter before the peritoneum is incised as a laceration at deeper levels can cause fistulas and infections (Araco et al, ; Satitniramai and Manonai, ). Although it has not yet been shown to be a risk factor, it has been stated that the use of a laparoscopic approach in general rather than a different technique could contribute to ureteric injuries (Satitniramai and Manonai, ). Recently, it was stated that the ureter lies 1.3–2.0 cm lateral to the uterosacral ligament between the sacrum and the level of the ischial spine (Siff et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Urinary tract injuries are a known complication of gynecologic surgery, occurring in 0.18% -0.80% of procedures [1] [2] [3]. Specifically, the most common injuries are to the bladder, accounting for 52% -75% of all urologic injuries [1] [2].…”
Section: Introductionmentioning
confidence: 99%